Preparation of Porous Ceramic Building Decoration Materials by Foaming Method and Research on Nanomechanical Properties - Hongyao Zhang (International Journal of Analytical Chemistry)
Because of its excellent properties, mullite porous ceramics are widely used in thermal insulation materials, catalyst carriers, gas-liquid filtration, separation materials, etc. At the same time, zirconia not only has the advantages of high melting point, good chemical stability, and high strength but also can significantly improve the strength of ceramics through phase transformation and particle dispersion in the matrix and is widely used in the reinforcement of ceramics. In this paper, using mullite powder as the raw material, Al2O3 and SiO2/ZrSiO4 as the starting material for the mullite self-bonding phase, and AlF3·3H2O, ZrO2, and Y2O3 as additives, the zirconia-reinforced mullite was prepared by the foaming-injection method. The volume density, linear shrinkage rate, microstructure, room temperature, etc. of nanozirconia-reinforced mullite porous ceramics were studied by the amount of the foaming agent, the amount of mullite self-bonding phase powder, the type and amount of additives, etc. Effects of mechanical properties and thermal conductivity were also analyzed. The research results show that zirconia-reinforced mullite porous ceramics were prepared with mullite powder and 6 wt% AlF3·3H2O as raw materials, and ZrO2 and Y2O3 as additives. Adding an appropriate amount of ZrO2 and Y2O3 can significantly improve the mechanical properties of porous ceramics. When ZrO2 is 6 wt% and Y2O3 is 8 wt%, the porosity is 66.4% and the flexural strength and compressive strength of porous ceramics with a large pore size of 168 μm can reach 14.3 MPa and 36.3 MPa, respectively, which are obviously better than the strength of mullite porous ceramics without adding Y2O3 (flexural strength 11.3 MPa, nanocompressive strength 29.4 MPa).